Graduate teaching assistants’ views of broken-into-parts physics problems: Preference for guidance overshadows development of self-reliance in problem solving - Melanie Good (American Physical Society, 2020)
We examined physics graduate teaching assistants’ views about introductory physics problem “types,” i.e., different ways of posing the same underlying physics problem, within the context of a semester-long teaching assistant (TA) professional development course. Here, we focus on TAs’ views about two types of broken-into-parts problems that involve the same underlying physics scenario. One of these problem types does not involve explicit calculation, while the other does. The TAs were asked to list the pros and cons of these two types of broken-into-parts problems, rank them compared to other problem types (e.g., traditional textbook problem not broken-into-parts, context-rich problem, and multiple-choice problem) with the same underlying scenario in terms of their instructional benefit and the level of challenge they might produce for their students, and describe when and how likely they would be to use these types of problems in their own classes in different instructional situations if they had complete control of teaching the class. TAs reported that they found the broken-into-parts problem type to be the most instructionally beneficial out of all the problem types because of the guidance such problems offer, and would use a broken-into-parts problem type often and in a variety of ways (e.g., homework assignments, exams, and quizzes). While providing guidance to students is an appropriate instructional approach, our findings from interviews suggest that many TAs may be motivated to assign broken-into-parts problems out of a desire to make the problem-solving process easy and/or less stressful for students, especially because they felt that introductory students may not be capable of breaking a problem into subproblems on their own. The instructional benefits of gradually removing the scaffolding support to help students develop self-reliance in solving problems appeared to be overlooked by most TAs. In particular, in written responses or in interviews, most TAs did not mention a long-term goal of helping students develop more independence in problem solving for which one may start with broken-into-parts problems and gradually transition to problems that are not broken into parts. While the study findings that provide a snapshot of TA views in the middle and at the end of a TA professional development course may only apply to graduate TAs at a similar large university, at those institutions, professional development of TAs should take into account these findings and help TAs reflect on the important role that removing scaffolding support gradually and providing adequate challenge can play in helping introductory students develop self-reliance and become independent, expertlike problem solvers.